Adverse events in anesthesiology: analysis based on the Logbook tool used by specializing physicians in Brazil - Pavão, Ana Luiza Braz; Mattos, Sérgio; Silva, Enis; Laguardia, Josué; Doellinger, Vanessa; Curi, Erick; Casali, Tolomeu; Takaschima, Augusto; Almeida, Armando; Albuquerque, Marcos; Nunes, Rogean (Brazilian journal of anesthesiology (Elsevier), 2019)
Logbook is a digital tool launched by the Brazilian Society of Anesthesiology in 2014 and has since been used. This tool allows physicians specializing in anesthesiology to record and store activities performed during the training period. This enabled a descriptive analysis of an extensive database of anesthetic procedures, as well as complications that occurred and were reported by these doctors. The present study includes the review of these data over a period of 2 years (2014–2015). O Logbook é uma ferramenta digital, lançada pela Sociedade Brasileira de Anestesiologia em 2014 e empregada desde então. Esta ferramenta permite, aos médicos em especialização em anestesiologia, o registro e o armazenamento das atividades executadas durante o período de treinamento. Isto possibilitou a análise descritiva de um extenso banco de dados dos procedimentos anestésicos, bem como das complicações ocorridas, relatadas por esses médicos. O presente estudo compreende a revisão desses dados num período de dois anos (2014–2015).